The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1017/s0954579417000062
|View full text |Cite
|
Sign up to set email alerts
|

Attachment in young children with incarcerated fathers

Abstract: The present study examined young children's attachment behaviors during paternal incarceration and reported on initial validity of a new measure used to rate children's attachment-related behaviors and emotions during visits in a corrections setting. Seventy-seven children, age 2 to 6 years, and their jailed fathers and current caregivers participated in the home visit portion of the study, whereas 28 of these children participated in the jail visit. The results indicated that 27% of children witnessed the fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 56 publications
1
52
0
7
Order By: Relevance
“…The quality of children's visits with their incarcerated parents is likely affected by institutional conditions (Shlafer, Loper, & Schillmoeller, 2015) that may vary from childfriendly (e.g., developmentally appropriate toys and family activities) to highly stressful (e.g., strict rules about children's behavior, no physical contact such as hugging or hand-holding). Research on the effects of visitation on child outcomes has been mixed, although to date, only one study has included systematically observed child behavior in the context of visits, and this work was conducted with fathers in jail (Poehlmann-Tynan, Burnson, Runion, & Weymouth, 2017).…”
Section: Parent-child Contactmentioning
confidence: 99%
“…The quality of children's visits with their incarcerated parents is likely affected by institutional conditions (Shlafer, Loper, & Schillmoeller, 2015) that may vary from childfriendly (e.g., developmentally appropriate toys and family activities) to highly stressful (e.g., strict rules about children's behavior, no physical contact such as hugging or hand-holding). Research on the effects of visitation on child outcomes has been mixed, although to date, only one study has included systematically observed child behavior in the context of visits, and this work was conducted with fathers in jail (Poehlmann-Tynan, Burnson, Runion, & Weymouth, 2017).…”
Section: Parent-child Contactmentioning
confidence: 99%
“…PI exposure creates more emotional issues and strain in the lives of children than other parental absences such as divorce or military deployment (Phillips & Gates, 2011;Schnittker & John, 2007;Turney, 2014). The process of PI may initially start pre-incarceration through the trauma of witnessing the arrest of a parent (Poehlmann-Tynan, Burnson, Runion, & Weymouth, 2017), to post-incarceration through the denial of housing and employment (Pager, 2003). Further, lack of access to transportation to the prison institution for parental visitation and communication barriers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, in the course of coediting the excellent papers in this Special Issue, several themes emerged repeatedly, which we believe merit some attention at the outset. As elaborated on below, these themes included the following: the value of studies of attachment in the context of atypical caregiving for producing methodological insights (e.g., Bailey, Tarabulsy, Moran, Pederson, & Bento, 2017; Kobak et al, 2017; Martin, Bureau, et al, 2017; Martin, Sturge-Apple, Davies, Romero, & Buckholz, 2017; Poehlmann-Tynan et al, 2017; Raby, Labella, et al, 2017; Raby, Yarger, et al, 2017); the continued search for biological mechanisms capable of explaining the origins and potentially enduring consequences of variation in early attachment experiences (Blaze & Roth, 2017; Fearon et al, 2017; Mulder et al, 2017; Quevedo et al, 2017; Thijssen et al, 2017); and the notable diversity of current attachment-related intervention efforts (Cassidy et al, 2017; Dubois-Comtois et al, 2017; Guild, Toth, Handley, Rogosch, & Cicchetti, 2017; Handley, Michl-Petzing, Rogosch, Cicchetti, & Toth, 2017; Humphreys, Nelson, Fox, & Zeanah, 2017; Schact et al, 2017; Suchman et al, 2017; Swain et al, 2017; Tereno et al, 2017). …”
mentioning
confidence: 99%